Traditional bullying, cyberbullying, and subjective well-being post-COVID-19 in Indonesia - Borualogo, Ihsana Sabriani; Saefudin, Muhamad Arif; Wahyudi, Hedi; Kusdiyati, Sulisworo (Jurnal Psikologi, 2024)
Previous research has highlighted bullying as a significant issue in Indonesia, with a notable increase in cyberbullying among adolescents during the COVID-19 pandemic, adversely affecting their psychological well-being. However, there has been limited discussion on bullying in the post-COVID-19 era. This study has three aims. The first is to examine the subjective well-being (SWB) of children who have either experienced bullying or have not been bullied after the pandemic. The second is to assess the occurrence of both traditional bullying (involving siblings and at school) and cyberbullying in Indonesia following COVID-19. The third aim is to investigate the factors linked to these forms of bullying post-pandemic. The participants were middle school students (N = 943; 57.2% girls, 45.0% in grade 7). The Children's Worlds Subjective Well-Being Scale with five items (CW-SWBS5) was employed to assess children's SWB. Separate measures were utilized for traditional and cyberbullying. Six factors—family, school climate, personal satisfaction, friendships, safety, and social media usage—were analyzed as independent variables using linear regression to determine their impact on bullying forms. The structural equation model (SEM) was applied to evaluate how these bullying types affect SWB. The findings revealed that sibling bullying and cyberbullying significantly influenced children’s SWB, with girls reporting lower SWB scores than boys. Cyberbullying emerged as the most prevalent form of bullying post-pandemic. A positive school climate was found to shield children from bullying. Cummins' theory of well-being homeostasis was employed to interpret the results. This study also discussed implications for educators and parents.